A Review of the Chemical, Biochemical and Antimicrobial Aspects of Turkish Otlu (herby) Cheese - Tarakci, Zekai; Temiz, Hasan (Wiley, 2009)
Otlu (herby) cheese, a traditional Turkish dairy product, is commonly made in Eastern Anatolia in Turkey. It is consumed in the various parts of Turkey, especially in the eastern and southeastern parts. Its popularity has been increasing because of industrialization of its production. It is manufactured from raw milk, is salty in taste and has a herby intense aroma because of the added herbs. The unusual processing steps of the cheese are that it is firmly filled in a plastic cheese container and stored under the soil during ripening. The flavour becomes highly acceptable after 3 months of ripening. The most common herbs used in the cheese are wild garlic (Allium sp.) but other herbs (Ferula sp., Prangos sp., Thymus sp., Mentha sp., Chaerophyllum macropodum and Silene vulgaris) are also used individually or as appropriate mixtures. The herbs give the cheese its flavour, but also extend the shelf life of the cheese. The aim of this review was to outline the manufacture and chemical, biochemical and antimicrobial properties of Otlu herby cheese.
Keywords: Antimicrobial Properties; Herbs; Lipolysis; Otlu (Herby) Cheese; Proteolysis